Um Estudo Exploratório sobre as Atitudes em Relação aos Conhecimentos Matemáticos de Professoras da Educação Infantil - Tortora, Evandro; Pirola, Nelson Antonio [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2020)
This article aims to present the results of an investigation on the attitudes of early childhood education teachers towards working with mathematical knowledge. In this study, 115 kindergarten teachers participated, who responded to a scale of attitudes towards working with mathematical knowledge in kindergarten. In this group, 55 teachers responded to a questionnaire. The analysis of the data showed that the majority of the teachers who answered the scale of attitudes tend to have more negative attitudes; however, the qualitative analysis of the questionnaires revealed more positive attitudes. In addition, it pointed out that the positive experiences in relation to mathematics had greater influence on the formation of the teachers' attitudes, whereas the negative experiences served as examples of practices to be put aside in their teaching activities.

Este artigo tem por objetivo apresentar os resultados de uma investigação sobre as atitudes de professoras da Educação Infantil frente aos conhecimentos matemáticos em suas práticas com as crianças. Participaram deste estudo 115 professoras de Educação Infantil que responderam a uma escala de atitudes em relação ao trabalho com conhecimentos matemáticos na Educação Infantil e, deste grupo, 55 professoras que responderam a um questionário. As análises dos dados mostraram que a maioria das professoras que respondeu à escala de atitudes tende a ser mais negativa; porém as análises qualitativas dos questionários revelaram atitudes mais positivas, bem como apontaram que as experiências positivas em relação à matemática tiveram maior influência na formação das atitudes das professoras e as experiências negativas serviram como exemplos de práticas a serem superadas em sua atividade docente.
An Exploratory Study on the Attitudes towards Mathematical Knowledge of Early Childhood Education Teachers
Keywords: Early childhood Education; Mathematics education; Teachers' behavior; Teachers' attitudes; Educação infantil; Educação matemática; Comportamento do professor; Atitude do professor